Dogs Detecting COVID-19 From Sweat and Saliva of Positive People: A Field Experience in Mexico - Mancilla-Tapia, Juan Manuel; Lozano-Esparza, Victoria; Orduña, Adrián; Osuna-Chávez, Reyna Fabiola; Robles-Zepeda, Ramón Enrique; Maldonado-Cabrera, Blayra; Bejar-Cornejo, Jorge Rubén; Ruiz-León, Iván; González-Becuar, Carlos Gabriel; Hielm-Björkman, Anna; Novelo-González, Ana; Vidal-Martínez, Victor Manuel (Frontiers in Medicine, 2022)
Context: Molecular tests are useful in detecting COVID-19, but they are expensive in developing countries. COVID-19-sniffing dogs are an alternative due to their reported sensitivity (> 80%) and specificity (> 90%). However, most of the published evidence is experimental, and there is a need to determine the performance of the dogs in field conditions. Hence, we aimed to test the sensitivity and specificity of COVID-19-sniffing dogs in the field. Methods: We trained four dogs with sweat and three dogs with saliva of COVID-19-positive patients, respectively, for 4.5 months. The samples were obtained from a health center in Hermosillo, Sonora, with the restriction to spend 5 minutes per patient. We calculated sensitivity, specificity and their 95% confidence intervals (CI). Results: Two sweat-sniffing dogs reached 76% and 80% sensitivity, with the 95% CI not overlapping the random value of 50%, and 75% and 88% specificity, with the 95% CI not overlapping the 50% value. The 95% CI of the sensitivity and specificity of the other two sweat dogs overlapped the 50% value. Two saliva-sniffing dogs had 70% and 78% sensitivity, and the 95% CI of their sensitivity and specificity did not overlap the 50% value. The 95% CI of the third dog’s sensitivity and specificity overlapped the 50% value. Conclusion: Four of the six dogs were able to detect positive samples of patients with COVID-19, with sensitivity and specificity values significantly different from random in the field. We considered the performance of the dogs promising because it is reasonable to expect that with gauze exposed for a longer time to sweat and saliva of people with COVID-19, their detection capacity would improve. The target is to reach the sensitivity range requested by the World Health Organization for the performance of an antigen test (≥ 80% sensitivity, ≥ 97% specificity). If so, dogs could become important allies for the control of the COVID-19 pandemic, especially in developing countries.